(untitled) (International Journal of Language, Literacy and Translation, 2025)
To achieve successful comprehension, a student has to be fully responsible of their own reading. However, being able to read proficiently carries a greater meaning now as more online materials are involved. Many students have been discovered to have difficulties mastering these non-linear readings as they require more sophisticated strategies compared to conventional linear readings. It is believed that being aware of one’s strategies could improve the quality of their comprehension and due to that, it is the objective of this study to find out the metacognitive online reading strategy awareness of the participants involved by using Survey of Online Reading Strategies (OSORS) established by Anderson (2003). 495 pre-university students in a Malaysian public university were chosen to be the participants of this study. At the time of the study, they were taking English Language course and English is their second language. From the study, it was discovered that all the participants were aware of most of the online reading strategies but with a very different level of awareness. The strategies under the Problem Solving (PROB) strategy was the highest and this category involves the use of specific techniques when readers encounter problems while reading online. The students involved portrayed their least involvement with the strategies under Support Strategy (SUP) where tools such as live chatting, note taking, and using pictures and graphs are used in assisting their online reading. Due to the inconsistency in the level of awareness discovered in the findings, it is concluded that metacognitive online reading strategies need to be included in the teaching curriculum and teachers too need to be aware and be an expert in utilising the strategies.